Overview of Coastal Communities Behavior in HIV/AIDS Testing, Indonesia: A Review - Saripa, Jamal; Hardianto (Yayasan Cipta Anak Bangsa (YCAB) Publisher, 2026)
Background: HIV/AIDS is a global health issue, including in Indonesia, which ranks fifth among countries with a high risk of HIV/AIDS, after South Africa, India, Mozambique, and Nigeria. It is estimated that approximately 1,700,000 people in Indonesia were living with HIV/AIDS in 2023. Coastal communities, particularly fishermen, require special attention in health development as they may be at risk of contracting HIV/AIDS. Therefore, efforts to prevent the spread of the disease are necessary through Voluntary Counseling and Testing (VCT) activities and educational sessions or talks on HIV/AIDS. Objective: This study aims to describe community behavior regarding HIV/AIDS testing in coastal areas of Indonesia. Methods: This research employed a Systematic Literature Review (SLR) approach to collect and analyze articles available online, particularly from Google Scholar and ResearchGate. Journal selection followed the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) framework. The analysis focused on HIV/AIDS testing in Indonesia’s coastal areas by identifying articles published between 2017 and 2025, using keywords such as Indonesia, HIV/AIDS, Coastal, Knowledge, Attitude, Service Access, and Family Support. Results: The study revealed that knowledge, attitudes, access to services, and family support are associated with HIV/AIDS testing among coastal communities in Indonesia. Limited knowledge due to a lack of information about HIV/AIDS, low education levels, and busy daily activities affects attitudes toward undergoing HIV testing. Difficult and distant access to health facilities discourages people from seeking testing services. Additionally, family support significantly influences a person's decision to take an HIV test. Conclusion: Based on the literature review on coastal community behavior toward HIV/AIDS testing, it can be concluded that knowledge, attitudes, service access, and family support are related to HIV/AIDS testing. These factors are influenced by limited access, inadequate health facilities, cultural, social, and economic conditions, low public awareness and education, and poor health-seeking behavior. Therefore, it is necessary to conduct HIV/AIDS education using appropriate methods. Keywords : Indonesia, HIV/AIDS, Coastal, Knowledge, Attitude, Service Access, Family Support, and Global Health